1961
DOI: 10.1577/1548-8659(1961)90[469:iowead]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Water Exchange and Dissolved Oxygen in Redds on Survival of Steelhead Trout Embryos

Abstract: A field study of spawning gravel conditions affecting the survival of steelhead trout (Salmo gairdneri Richardson) embryos was conducted in two small streams in the Alsea River Basin in Lincoln County, Oregon, from February to June 1959. Holes 10 inches deep, approximating natural redds. were dug in arbitrarily selected spawning locations. Plastic mesh sacks containing gravel and 100 fertilized trout eggs were placed in the upstream end of each hole. A standpipe was placed in the lower end of each excavation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
91
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(94 citation statements)
references
References 6 publications
2
91
0
Order By: Relevance
“…The data also indicated that large variations of permeability can occur within a short distance. Coble (1961) found that permeability values varied at sites only 15 cm apart. Based on results from Kondolf et al (2008) the zone of influence for each standpipe was less than a 20 cm radius.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The data also indicated that large variations of permeability can occur within a short distance. Coble (1961) found that permeability values varied at sites only 15 cm apart. Based on results from Kondolf et al (2008) the zone of influence for each standpipe was less than a 20 cm radius.…”
Section: Discussionmentioning
confidence: 97%
“…summarized prior studies showing that the survival of salmonid embryos is positively correlated to permeability (r 2 = 0.85). Coble (1961) found that there was no relationship between permeability and survival, but rather a relationship between apparent velocity and survival. The difference is that permeability describes the physical capacity of the substrate to transmit water whereas apparent velocity describes the rate of flow of water through a unit area of substrate.…”
Section: Introductionmentioning
confidence: 90%
“…An increase in the fine material within the bed matrix reduces intragravel water velocity, which in turn lowers incubation success by reducing the amount of oxygen delivered to eggs (Chapman 1988). Although results vary, intragravel dissolved oxygen levels from 2 to 8 mg/L are required for successful incubation of salmonid eggs (Coble 1961;Sowden and Power 1985;Bjornn and Reiser 1991). Successful incubation, therefore, depends not on the structure of the bed framework but rather on the amount of fine material comprising the bed matrix.…”
Section: Assessment Of Substrate Quality Of Fall Chinook Salmon Spawnmentioning
confidence: 99%
“…We estimated survival to emergence using specific discharge results and found survival rates that were very low. For example, using relationships published by Coble (1961), the survival estimates in spawning areas ranged from less than 1% to 10%. In nonspawning locations, the highest estimated survival to emergence was less than 1%.…”
Section: Riverbed Permeabilitymentioning
confidence: 99%
“…While velocity may play an important role in these processes, IFC do not appear to be utilizing this habitat feature as a spawning site selection cue. In a study on steelhead trout (Salmo gairdneri) embryos, Coble (1961) found that when velocity varied but oxygen concentrations remain constant there was no survival difference during incubation. Dissolved oxygen, rather than velocity, may be used as a habitat selection 62 cue.…”
Section: Traditional Habitat Model Parametersmentioning
confidence: 99%